Pemberdayaan literasi digital siswa SMA melalui pelaksanaan try out dengan sistem computer-based test di SMA Negeri 1 Karangnongko - Muhammad Fakhri Ar Rouf; Yasinta Harfahra Inna Dewi; Deddy Rahmadi (Nur Science Institute, 2026)
This community service program aims to improve the digital readiness of 12th-grade students at SMA Negeri 1 Karangnongko in preparation for the Computer-Based National Selection Test (SNBT). Initial observations indicated that assessment activities were still conducted using paper-based methods, limiting students’ exposure to digital examinations. To address this issue, a Computer-Based Test (CBT) system was implemented through socialisation, guided practice, and technical assistance during a try-out session. The program involved 172 students, all of whom successfully accessed and completed the CBT simulation. In addition, 118 students provided feedback through questionnaires, indicating positive responses toward system usability and examination experience. Most students reported that the CBT system was easy to use, helped reduce anxiety, and improved familiarity with computer-based examinations. These results indicate an improvement in students’ digital readiness, particularly in operational skills and examination navigation. Furthermore, the implemented CBT system can be reused independently by the school, providing sustainable benefits for future digital assessment activities.